2005
DOI: 10.1258/0956462054094024
|View full text |Cite
|
Sign up to set email alerts
|

Verification of clinical samples, positive in AMPLICOR Neisseria gonorrhoeae polymerase chain reaction, by 16S rRNA and gyrA compared with culture

Abstract: We compared 956 samples for AMPLICOR Neisseria gonorrhoeae polymerase chain reaction (PCR) (Roche) with species verification using the 16S rRNA gene to verification using gyrA gene. Control was the culture method. The gyrA verification uses pyrosequencing of the quinolone resistance-determining region of gyrA. Of 52 samples with optical density >/=0.2 in PCR, 27 were negative in culture, two samples from pharynx were false negative in culture and four samples from pharynx were false positives in verification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 137 publications
(246 reference statements)
1
9
0
Order By: Relevance
“…Despite the fact that a few ciprofloxacin‐resistant N. gonorrhoeae strains without alterations in the QRDR of the gyrA have been reported (15–17), the present study supports previous studies (6–9) of pyrosequencing of the QRDR in the gyrA gene as an effective molecular method to indicate resistance to ciprofloxacin in N. gonorrhoeae. However, the method is useful for N. gonorrhoeae and presumably for N. meningitidis , but not for other Neisseria spp.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Despite the fact that a few ciprofloxacin‐resistant N. gonorrhoeae strains without alterations in the QRDR of the gyrA have been reported (15–17), the present study supports previous studies (6–9) of pyrosequencing of the QRDR in the gyrA gene as an effective molecular method to indicate resistance to ciprofloxacin in N. gonorrhoeae. However, the method is useful for N. gonorrhoeae and presumably for N. meningitidis , but not for other Neisseria spp.…”
Section: Resultssupporting
confidence: 86%
“…Consequently, samples that give no PCR product can be verified as non‐ N. gonorrhoeae. In a previous study Airell et al (6) showed that out of 24 N. gonorrhoeae culture‐negative pharynx samples, 16 were positive in AMPLICOR N. gonorrhoeae PCR (Roche Diagnostics). N. gonorrhoeae species verification using the 16S rRNA gene was negative in 14 of these samples and in all 16 with verification with the gyrA gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even highly specific assays may have unacceptably low positive predictive values in such settings. Although a validation study in Washington State (0.5% prevalence) found that only 3% of specimens positive for gonorrhea by APTIMA COMBO 2 assay were potentially falsely positive [14], false-positive N. gonorrhoeae test results have been a problem with the COBAS AMPLICOR CT/NG assay (Roche Molecular Systems), and confirmatory testing is required in lowprevalence populations [15,[30][31][32]. Adopting selective testing criteria could reduce the risk of false-positive results by increasing the prevalence of infection among those tested.…”
Section: Notementioning
confidence: 99%